Knowledge and Awareness of Microenterprises Regarding Green Accounting - Syukriyana, Dzikriya; Prijanto, Tulus; Veno, Andri (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2026)
Awareness of environmental sustainability has become a global concern, including in the business world. Although environmental issues are more often associated with large-scale industries, microenterprises also play an important role in preventing environmental damage through their business activities. By understanding the level of knowledge and awareness of micro-enterprises regarding green accounting, we can take the necessary steps to support its implementation. This study aims to determine the level of knowledge and awareness of green accounting among micro-enterprises. The concept of green accounting, in conjunction with Islamic teachings on moral values, ethics, and the goal of public benefit, closely aligns with Islamic values of environmental responsibility, justice, and accountability. This study is a survey study. Data was collected directly from respondents through a questionnaire. The collected questionnaire data were analyzed using descriptive statistics. The majority of respondents believe that green accounting is important because it can improve business image, increase cost efficiency, and attract more customers. However, this high level of awareness has not been matched by its implementation. This study recommends that green accounting be implemented in microenterprises with the simplest approaches, such as using environmentally friendly raw materials, waste management, recycling, and green energy.